HUBUNGAN KUALITAS PELAYANAN KESEHATAN BERBASIS HOME CARE DENGAN KEPUASAN PASIEN DI WILAYAH KERJA PUSKESMAS LAYANG - Andi Tania Yasni Aldini; St Rosmanely; Indar (Kampurui Jurnal Kesehatan Masyarakat, 2023)
Background: Quality of service can be said to be qualified if it gives satisfaction to patients. As time goes by, with increasing levels of education and people's incomes, the demands of the community to obtain quality health services are also increasing. Purpose: This study aims to determine the relationship between the quality of home care-based health services and patient satisfaction in the work area of the Layang Public Health Center, Makassar City. Methods: This type of research is quantitative with a cross sectional study approach. The population in this study were 159 home care patients in the working area of the Layang Health Center in Makassar City. The sampling technique used simple random sampling with a total sample of 60 respondents. Data collection was carried out using a questionnaire/checklist sheet. The research results were analyzed using SPSS. Results: In general, from the research results of each research variable, it was found that the majority of respondents expressed satisfaction with the quality of Home Care services in the work area of the Layang Health Center. The results of the correlation analysis using the chi-square test (p < 0.05) showed that there was a relationship between the dimensions of technical competence (p = 0.000), human relations (p = 0.02), and accuracy time (p = 0.000) with patient satisfaction. That is, the better the quality of services provided, the higher the resulting patient satisfaction. Conclusion: There is a relationship between the dimensions of technical competence, human relations, safety, continuity, and timeliness of possession with patient satisfaction. It is hoped that the Layang Health Center can improve the quality of services provided to home care patients, especially in the timeliness of patient examinations